2002
DOI: 10.1007/s12031-002-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of indole-3-propionic acid (OXIGON™) for alzheimer’s disease

Abstract: The accumulation of amyloid-beta and concomitant oxidative stress are major pathogenic events in Alzheimer's disease. Indole-3-propionic acid (IPA, OXIGON) is a potent anti-oxidant devoid of pro-oxidant activity. IPA has been demonstrated to be an inhibitor of beta-amyloid fibril formation and to be a potent neuroprotectant against a variety of oxidotoxins. This review will summarize the known properties of IPA and outline the rationale behind its selection as a potential disease-modifying therapy for Alzheime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 29 publications
1
98
0
Order By: Relevance
“…Conversely, a different set of enteric bacteria has been implicated in the metabolic transformation of indole to indole-3-propionic acid (IPA) (27). IPA, also identified only in the plasma of conv mice, has been shown to be a powerful antioxidant (28), and is currently being investigated as a possible treatment for Alzheimer's disease (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a different set of enteric bacteria has been implicated in the metabolic transformation of indole to indole-3-propionic acid (IPA) (27). IPA, also identified only in the plasma of conv mice, has been shown to be a powerful antioxidant (28), and is currently being investigated as a possible treatment for Alzheimer's disease (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…IPA has been shown to be a powerful antioxidant [71] and has been considered as a possible treatment for Alzheimer's disease [72] due to its ability to protect neurons and neuroblastoma cells against oxidative damage and death [73,74].…”
Section: Indole-3-propionic Acidmentioning
confidence: 99%
“…Pharmacological studies of indolic compounds reported a wide variety of important biological properties such as anti-inflammatory [2,3], analgesic [3], antibacterial [4], antifungal [5], neuroprotective [6,7], antitumour [8][9][10] and antioxidant properties [11].…”
Section: Introductionmentioning
confidence: 99%